The development and initial validation of a scale to measure group functioning. - Bleekers, Robin (My University, 2013)
The aim of this study was to develop a scale to measure group functioning in work groups. The scale was developed based on the Integrative Model of Group Development. There were 76 individuals who participated in the study. There were 15 groups that participated in this study. The sample was drawn from an organisation in Johannesburg. The research design was non-experimental and cross-sectional in nature. The data collected were analysed using factor analysis, Cronbach’s Alpha coefficient and discriminant analysis. The results showed that the overall scale had two subscales which showed strong reliabilities. The implications of the findings are that further research is needed to match stages of group development with the behaviour of individuals in organisations. The findings indicate that more research on group functioning in the South African work context is required.
Keywords: Teams in the workplace--South Africa.; Social groups--Psychological aspects.; Organizational behavior--South Africa.